PEMANFAATAN BIG DATA UNTUK PERCEPATAN PROSES UNDERWRITING SEBAGAI STRATEGI KOMUNIKASI MARKETING TERPADU PERUSAHAAN ASURANSI JIWA - Annisa Khairani; Irwansyah Irwansyah (Jurnal Nomosleca, 2018)
Abstract In the fast-paced era like now, the demand for effective and efficient business processes is increasing, not least in the insurance industry. One of the things that can increase the acceleration of business processes is the utilization of big data in the industry. Big data is important, those who can take advantage of big data will have a strong and fast base in making business decisions including the insurance company Allianz. Utilizing big data in accelerating business processes in the insurance industry, especially at PT. Allianz Life Indonesia insurance occurs in the process of accelerating underwriting with an automatic underwriting system so that it can be one of the selling points in the marketing process of corporate communications to customers. The presence of this automatic underwriting system replaces the role of human underwriters by the system so that the role of underwriters will be increased to process prospective customer data that is more complex and requires analysis that is not contained in the system. The company expands into new markets by highlighting the advantages of a faster and simpler underwriting process that is supported by the use of Big Data and more sophisticated analysis as one of the marketing communication strategies. The purpose of this conceptual paper is to explain how big data management can be used as one of the insurance company's marketing communication strategies. Keywords: Big Data, Underwriting, Communication Marketing StrategyDOI : https://doi.org/10.26905/nomosleca.v4i2.2546